2019
DOI: 10.1007/s40090-019-0183-6
|View full text |Cite
|
Sign up to set email alerts
|

Thermal performance of a micro heat exchanger (MHE) working with zirconia-based nanofluids for industrial cooling

Abstract: An experimental investigation was performed with the view to assess the heat transfer characteristics of a water-based nanofluid in a micro heat exchanger employed to quench a high heat flux heater for industrial and microelectronic cooling applications. The experiments were conducted at heat fluxes 10-70 kW/m 2 and for nanofluids at various mass concentrations of 0.1-0.3% and passing flow rates of 0.1-5 l/min. Thermo-physical properties of the nanofluid including thermal conductivity, heat capacity, density a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…Table 2 shows the TC of Silver nano-particle-containing water as a function of nano-particle concentrations ranging from 1 to 8%. Silver nano-fluids' TC rises in a linear relationship with nano-particle concentration [30]. Table 3 shows the TC of water with 1-8 percent copper nanoparticles, as well as the correlation of consequences by hypothetical TC models [31].…”
Section: Table 1 Tc Of Nanofluids (Water + Aluminum)mentioning
confidence: 99%
“…Table 2 shows the TC of Silver nano-particle-containing water as a function of nano-particle concentrations ranging from 1 to 8%. Silver nano-fluids' TC rises in a linear relationship with nano-particle concentration [30]. Table 3 shows the TC of water with 1-8 percent copper nanoparticles, as well as the correlation of consequences by hypothetical TC models [31].…”
Section: Table 1 Tc Of Nanofluids (Water + Aluminum)mentioning
confidence: 99%
“…For instance, Sarafraz et al [4] studied the utilization of liquid metal nano-suspension in a rectangular microchannel with the view to develop a new insight for the fabrication of solar thermal receiver working with liquid metals. Also, Nikkhah and Nakhjavani [5] investigated the heat-transfer characteristics of zirconia nanofluid in micro-heat exchangers employed for micro-electronic cooling applications, while Sadeghinezhad et al [6] studied the performance of turbulent heat transfer of graphene nanofluids in horizontal stainless-steel tubes. Additionally, Abdel Hafiz et al [7] investigated the heat-transfer characteristics of graphene nanoplatelets/water nanofluid in a micro-heat exchange.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous research articles available in the literature 1352 attributed to fluid flow and heat transfer characteristics of nanofluid in microchannels as well as MCHS. Vafaei and Wen 13,14 experimentally measured the effect of nanoparticle concentration (1-7vol.%) and volume flow rate (8-20ml/min) on fluid flow and heat transfer characteristics of Al2O3/water nanofluid in a circular microchannel (Di=510μm,t=160…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the maximum enhancement in HTC was obtained up to 21.7% for Al2O3/water nanofluid with nanoparticle concentration of 1.0vol.% as compared to DW. Nikkhah and Nakhjavani 42,43 experimentally measured the effect of nanoparticle concentration (0.1-0.3wt.%) and volume flow rate (1-5l/min) on fluid flow and heat transfer characteristics of ZrO 2 /water nanofluid flowing in a MCHS (200μm×200μm,L=50mm and N = 25) at different heat fluxes ranging from 10kW/m2 to 70kW/m2. The results showed that the maximum enhancements in friction factor and average HTC were achieved up to 13.9% and 17.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation